Simultaneous recovery of chromium and destruction of organics from LCD manufacturing process wastewater by supercritical water oxidation - Veriansyah, Bambang; Kim, Jae-Duck; Lee, Youn-Woo (ELSEVIER SCI LTD, 2007)
The effectiveness of supercritical water oxidation (SCWO) process for the simultaneous recovery of chromium and destruction of organics from liquid crystal display (LCD) manufacturing process wastewater was investigated. The experiments were performed in an isothermal continuous-flow tubular reactor and H2O2 was used as an oxidant. The reaction temperatures ranged from 400 to 605 degrees C and the residence times ranged from 15 to 31 s at a fixed pressure of 25 MPa. The effect of temperature, oxidant concentration and residence time on chromium recovery and chemical oxygen demand (COD) conversion was investigated. The results of this study demonstrated that the SCWO process recovered chromium and decreased chemical oxygen demand up to 99.3% and 99.9%, respectively. The analyses showed that chromium are recovered as chromium oxide (alpha-HCrO2 and Cr2O3). The SCWO process is an effective technique for simultaneously recovering chromium and for the destruction of hazardous organics in the LCD manufacturing process wastewater. Our study showed that there are two consequent reactions, chromium recovery reaction (hydrolysis) followed by the organic decomposition reaction (oxidation). The recovery of chromium can be achieved without major organic decomposition. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: LIQUID WASTE; REMOVAL; METALS; COBALT; DECOMPOSITION; PRETREATMENT; OXIDANT; SILICA; COPPER; IONS